2002
DOI: 10.1002/ijc.10748
|View full text |Cite
|
Sign up to set email alerts
|

Progression of microsatellite instability from premalignant lesions to tumors of the head and neck

Abstract: The role of microsatellite alterations other than loss of heterozygosity (LOH) in the progression of benign epithelium to head-and-neck squamous cell cancer (HNSCC) has not been previously described. As the severity of the dysplasia increases at the microscopic level, there is an increase in the prevalence of LOH as defined by microsatellite analysis. Other alterations have been detected in the form of microsatellite instability (MSI), represented by insertions or deletions of base pairs. It is unknown, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 12 publications
6
32
0
1
Order By: Relevance
“…Upregulation of NOTCH4 is associated with breast and mammary cancer (Weng and Aster, 2004). Independent confirmation of our observations is provided by recent expression array studies, which found significant upregulation of JAG1 and NOTCH4 in oral SCC compared to normal tissue (Leethanakul et al, 2000;Ha et al, 2003). These studies together with the data reported here indicate a role for deregulation of notch signaling in oral cancer.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Upregulation of NOTCH4 is associated with breast and mammary cancer (Weng and Aster, 2004). Independent confirmation of our observations is provided by recent expression array studies, which found significant upregulation of JAG1 and NOTCH4 in oral SCC compared to normal tissue (Leethanakul et al, 2000;Ha et al, 2003). These studies together with the data reported here indicate a role for deregulation of notch signaling in oral cancer.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, notch signaling promotes differentiation in skin (Lefort and Dotto, 2004) and loss of function of notch is permissive for tumor formation in mouse models (Nicolas et al, 2003). Although two expression array studies found upregulation of some members of the wnt and notch signaling pathways in head and neck SCC (Leethanakul et al, 2000;Ha et al, 2003), the hedgehog and notch pathways have not been previously characterized in oral squamous cell tumorigenesis. Therefore, we investigated whether expression levels of other members of the hedgehog and notch pathways were altered in oral SCC.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies show that invasive carcinomas manifest more MSI than precursor lesions, suggesting progressive accumulation of MSI during tumor development 12,28 (Table 1). Furthermore, precursor lesions that show MSI are more prone to progress to HNSCC.…”
Section: What Are Msi and Loh?mentioning
confidence: 99%
“…Some of the markers can be used to determine premalignant conditions before the appearance of a histopathologically evident abnormality (8).…”
Section: Introductionmentioning
confidence: 99%